Safety and tolerability of the first-in-class agent CPI-613 in combination with modified FOLFIRINOX in patients with metastatic pancreatic cancer: a single-centre, open-label, dose-escalation, phase 1 trial. Issue 6 (June 2017) - Alistar, Angela; Morris, Bonny B; Desnoyer, Rodwige; Klepin, Heidi D; Hosseinzadeh, Keyanoosh; Clark, Clancy; Cameron, Amy; Leyendecker, John; D'Agostino, Ralph; Topaloglu, Umit; Boteju, Lakmal W; Boteju, Asela R; et al.
Summary: Background: Pancreatic cancer statistics are dismal, with a 5-year survival of less than 10%, and more than 50% of patients presenting with metastatic disease. Metabolic reprogramming is an emerging hallmark of pancreatic adenocarcinoma. CPI-613 is a novel anticancer agent that selectively targets the altered form of mitochondrial energy metabolism in tumour cells, causing changes in mitochondrial enzyme activities and redox status that lead to apoptosis, necrosis, and autophagy of tumour cells. We aimed to establish the maximum tolerated dose of CPI-613 when used in combination with modified FOLFIRINOX chemotherapy (comprising oxaliplatin, leucovorin, irinotecan, and fluorouracil) in patients with metastatic pancreatic cancer. Methods: In this single-centre, open-label, dose-escalation phase 1 trial, we recruited adult patients (aged ≥18 years) with newly diagnosed metastatic pancreatic adenocarcinoma from the Comprehensive Cancer Center of Wake Forest Baptist Medical Center (Winston-Salem, NC, USA). Patients had good bone marrow, liver and kidney function, and good performance status (Eastern Cooperative Oncology Group [ECOG] performance status 0–1). We studied CPI-613 in combination with modified FOLFIRINOX (oxaliplatin at 65 mg/m 2, leucovorin at 400 mg/m 2, irinotecan at 140 mg/m 2, and fluorouracil 400 mg/m 2 bolus followed by 2400 mg/m 2 over 46 h). We applied a two-stage dose-escalation scheme (single patient and traditional 3+3 design). In the single-patient stage, one patient was accrued per dose level. The starting dose of CPI-613 was 500 mg/m 2 per day; the dose level was then escalated by doubling the previous dose if there were no adverse events worse than grade 2 within 4 weeks attributed as probably or definitely related to CPI-613. The traditional 3+3 dose-escalation stage was triggered if toxic effects attributed as probably or definitely related to CPI-613 were grade 2 or worse. The dose level for CPI-613 for the first cohort in the traditional dose-escalation stage was the same as that used in the last cohort of the single-patient dose-escalation stage. The primary objective was to establish the maximum tolerated dose of CPI-613 (as assessed by dose-limiting toxicities). This trial is registered withClinicalTrials.gov, numberNCT01835041, and is closed to recruitment. Findings: Between April 22, 2013, and Jan 8, 2016, we enrolled 20 patients. The maximum tolerated dose of CPI-613 was 500 mg/m 2 . The median number of treatment cycles given at the maximum tolerated dose was 11 (IQR 4–19). Median follow-up of the 18 patients treated at the maximum tolerated dose was 378 days (IQR 250–602). Two patients enrolled at a higher dose of 1000 mg/m 2, and both had a dose-limiting toxicity. Two unexpected serious adverse events occurred, both for the first patient enrolled. Expected serious adverse events were: thrombocytopenia, anaemia, and lymphopenia (all for patient number 2; anaemia and lymphopenia were dose-limiting toxicities); hyperglycaemia (in patient number 7); hypokalaemia, hypoalbuminaemia, and sepsis (patient number 11); and neutropenia (patient number 20). No deaths due to adverse events were reported. For the 18 patients given the maximum tolerated dose, the most common grade 3–4 non-haematological adverse events were hyperglycaemia (ten [55%] patients), hypokalaemia (six [33%]), peripheral sensory neuropathy (five [28%]), diarrhoea (five [28%]), and abdominal pain (four [22%]). The most common grade 3–4 haematological adverse events were neutropenia (five [28%] of 18 patients), lymphopenia (five [28%]), anaemia (four [22%], and thrombocytopenia in three [17%]). Sensory neuropathy (all grade 1–3) was recorded in 17 (94%) of the 18 patients and was managed with dose de-escalation or discontinuation per standard of care. No patients died while on active treatment; 11 study participants died, with cause of death as terminal pancreatic cancer. Of the 18 patients given the maximum tolerated dose, 11 (61%) achieved an objective (complete or partial) response. Interpretation: A maximum tolerated dose of CPI-613 was established at 500 mg/m 2 when used in combination with modified FOLFIRINOX in patients with metastatic pancreatic cancer. The findings of clinical activity will require validation in a phase 2 trial. Funding: Comprehensive Cancer Center of Wake Forest Baptist Medical Center.